PERAN KOMITE AUDIT, DEWAN KOMISARIS DAN AUDIT INTERNAL TERHADAP PENCEGAHAN FRAUD SERTA IMPLIKASINYA DALAM PENINGKATAN KINERJA PERUSAHAAN (Survei pada Emiten Manufaktur Di Bursa Efek Indonesia) - Tulus Suryanto (Indonesian Journal of Economics and Business, 2011)
This research was purposed to test and analyze the roles of audit committee, board of commissioner, and internal audit in preventing fraud and its implications in improving firm’s performance. Population in this research was manufacture listed in Indonesia Stock Exchange and samples were taken using simple random sampling. The population was 136 manufacture firms, and using Slovin Formula, samples were 102. The data type in this research was primary data taken from questionnaire distribution to all respondents; they were members of audit committee, board of commissioner, and internal audit.  All data were analyzed using path analysis with LISREL 8.70 PROGRAM.            The exogenous variables were the roles of audit committee, board of commissioner, and internal audit. The endogenous variables were fraud prevention and firm’s performance improvement. This research showed the positive correlation between the roles of audit committee, commissioner board, and internal audit in preventing fraud and in improving performance of manufacture listed in Indonesia stock exchange. This positive correlation occurred because of the synergy of roles of audit committee, board of commissioner, and internal audit to conduct monitoring roles to the executive tasks. Then, their roles simultaneously had positive roles in preventing fraud. This indicated that the more effective the roles of audit committee, board of commissioner, and internal audit would able to prevent fraud occurring in firms. In other words the roles of audit committee board of commissioner, and internal audit simultaneously or partially affect the fraud prevention, and had implication to the performances of manufacture listed in Indonesia stock exchange.